2002
DOI: 10.1034/j.1600-0854.2002.030303.x
|View full text |Cite
|
Sign up to set email alerts
|

Type IVB Secretion by Intracellular Pathogens

Abstract: A growing number of pathogens are being found to possess specialized secretion systems which they use in various ways to subvert host defenses. One class, called type IV, are defined as having homology to the conjugal transfer systems of naturally occurring plasmids. It has been proposed that pathogens with type IV secretion systems have acquired and adapted the conjugal transfer systems of plasmids and now use them to export toxins. Several well-characterized intracellular pathogens, including Legionella pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
132
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 60 publications
0
132
0
3
Order By: Relevance
“…They bear Walker A (motif I) and B (motif II or DExx box) NTP-binding sequences [88] and may use the energy of Rhizobium etli bacterium; N2-fixation [154] Sinorhizobium meliloti bacterium; N2-fixation [14,15,17] Shigella flexneri plasmid ColIb P9 bacterium; diarrhoea / dysentery [155] Bartonella henselae and tribocorum bacterium; cat scratch disease, bacteremia [156][157][158][159][160] Campylobacter jejuni bacterium; bacterial diarrhoea [161,162] Toxoplasma gondii protozoon; toxoplasmosis (encephalitis) [54] Leishmania donovani protozoon; leishmaniasis [54] Mycobacterium tuberculosis bacterium; tuberculosis [54] Bordetella bronchiseptica bacterium; bronchitis [14,15,17] Enterobacter aerogenes bacterium; nosocomial infections [11] Actinobacillus actinomycetemcomitans bacterium; periodontitis [14,15,17,163,164] Escherichia coli bacterium; diarrhea [11] Caulobacter crescentus bacterium; non-pathogenic [14,15,17] Coxiella burnetii bacterium; acute febrile disease, endocarditis, pneumonitis [165,166] Thiobacillus ferroxidans bacterium; iron oxidation [14,15,17] Wolbachia intracellular symbiont of arthropods; sexual alterations in host [167,168] Ralstonia eutrophantus bacterium; heavy-metal resistance [11,169] Salmonella typhi, typhimurium and enteriditis bacterium; typhus, salmonellosis …”
Section: Transfer Factors In Conjugative Type-iv Secretionmentioning
confidence: 99%
“…They bear Walker A (motif I) and B (motif II or DExx box) NTP-binding sequences [88] and may use the energy of Rhizobium etli bacterium; N2-fixation [154] Sinorhizobium meliloti bacterium; N2-fixation [14,15,17] Shigella flexneri plasmid ColIb P9 bacterium; diarrhoea / dysentery [155] Bartonella henselae and tribocorum bacterium; cat scratch disease, bacteremia [156][157][158][159][160] Campylobacter jejuni bacterium; bacterial diarrhoea [161,162] Toxoplasma gondii protozoon; toxoplasmosis (encephalitis) [54] Leishmania donovani protozoon; leishmaniasis [54] Mycobacterium tuberculosis bacterium; tuberculosis [54] Bordetella bronchiseptica bacterium; bronchitis [14,15,17] Enterobacter aerogenes bacterium; nosocomial infections [11] Actinobacillus actinomycetemcomitans bacterium; periodontitis [14,15,17,163,164] Escherichia coli bacterium; diarrhea [11] Caulobacter crescentus bacterium; non-pathogenic [14,15,17] Coxiella burnetii bacterium; acute febrile disease, endocarditis, pneumonitis [165,166] Thiobacillus ferroxidans bacterium; iron oxidation [14,15,17] Wolbachia intracellular symbiont of arthropods; sexual alterations in host [167,168] Ralstonia eutrophantus bacterium; heavy-metal resistance [11,169] Salmonella typhi, typhimurium and enteriditis bacterium; typhus, salmonellosis …”
Section: Transfer Factors In Conjugative Type-iv Secretionmentioning
confidence: 99%
“…27 Our group has shown that Cb survives and replicates in a large replicative vacuole (C. burnetii-replicative vacuoles (CRVs)) with clear autophagic features. 28 Besides, autophagy induction before infection, as well as the overexpression of proteins involved in this pathway (i.e.…”
mentioning
confidence: 99%
“…22 Consequently, inflammasomes assemble and activate caspase 1 by a mechanism that requires the JNK signal transduction pathway. When the contamination is scant, macrophages elevate autophagy, a membrane trafficking pathway that captures the pathogen within membranes derived from the early secretory pathway for delivery to degradative lysosomes.…”
mentioning
confidence: 99%